Nicotine Modulates MyD88-Dependent Signaling Pathway in Macrophages during Mycobacterial Infection - Dania AlQasrawi; Saleh A. Naser (Microorganisms, 2020)
Recently, we reported that cigarette smoking, and especially nicotine, increases susceptibility to mycobacterial infection and exacerbates inflammation in patients with Crohn’s disease (CD). The macrophagic response to Mycobacterium avium subspecies paratuberculosis (MAP) in CD and Mycobacteria tuberculosis (MTB) continues to be under investigation. The role of toll-like-receptors (TLRs) and cytoplasmic adaptor protein (MyD88) in proinflammatory response during Mycobacterial infection has been suggested. However, the mechanism of how nicotine modulates macrophage response during infection in CD and exacerbates inflammatory response remain unclear. In this study, we elucidated the mechanistic role of nicotine in modulating MyD88-dependent/TLR pathway signaling in a macrophage system during mycobacterial infection. The data demonstrated that MAP infection in THP-1 derived macrophages was mediated through TLR2 and MyD88 leading to increase in IL-8 in expression and production. On the other hand, LPS-representing, Gram-negative bacteria mediated macrophage response through TLR4. Blocking TLR2 and TLR4 with antagonists voided the effect of MAP, and LPS, respectively in macrophages and reversed response with decrease in expression of iNOS, TNF-α and IL-8. Interestingly, nicotine in infected macrophages significantly (1) downregulated TLR2 and TLR4 expression, (2) activated MyD88, (3) increased M1/M2 ratio, and (4) increased expression and secretion of proinflammatory cytokines especially IL-8, as seen in CD smokers. We also discovered that blocking macrophages during MAP infection with MyD88 antagonist significantly decreased response which illustrates the key role for MyD88 during infection. Surprisingly, dual treatment of MAP-infected macrophages with MyD88 antagonist and nicotine absolutely impaired immune response and decreased MAP viability, which clearly validate the inflammatory role of nicotine in macrophages through TLR2/MyD88 pathway during infection. This is the first report to describe the mechanism by which nicotine modulates TLR2/MyDD88 and exacerbates inflammation in CD smokers associated with infection.